Development of Energy Supply Infrastructure Based on Industry 4.0 (on the Example of Ukraine and Turkey) - Trofymenko, Olena; Voitko, Serhii; Naraievskyi , Serhii (Ekonomika, 2022)
The object of research was to identify the field of renewable energy for ensuring the process of gradual transition from traditional energy to carbon-free technologies. The article compares the opportunities for energy development, taking into account current trends in sustainable development. The conducted analysis of energy resources in the section of renewable energy is based on the processing of available sources of analytical and statistical information. The study investigates the structure and features of the functioning of the energy sector of Ukraine and Turkey. There have been revealed several common problems of functioning of energy spheres in Ukraine and Turkey. The article investigates the possibilities of using technological solutions and principles of Industry 4.0 in ensuring energy security through the development of the electric car market. The analysis consists of calculations of the efficient functioning of solar and wind energy for Ukraine and Turkey. The article provides recommendations for the development of possible mutually beneficial cooperation between Ukraine and Turkey in the field of renewable energy.
Keywords: energy market transformation; renewable energy; Industry 4.0; installed capacity efficiency